ANALISIS PERAN MIKROHIDRO DALAM MENANGGULANGI KRISIS PASOKAN LISTRIK: Analisis Peran Mikrohidro dalam Menanggulangi Krisis Pasokan Listrik - Fauzan Afif (Institut Riset dan Publikasi Indonesia, 2025)
The electricity supply crisis is still a major problem in various remote areas in Indonesia, which has a negative impact on economic growth, education, and community welfare. To overcome this problem, the use of renewable energy such as Microhydro Power Plants (PLTMH) is one of the relevant and sustainable solutions. This study aims to analyze the role of microhydro in overcoming the electricity supply crisis, as well as identifying supporting and inhibiting factors in its implementation. The research method used is a qualitative-descriptive approach with data collection techniques through literature studies, interviews, and field observations in areas that have developed PLTMH. The results of the study show that microhydro is able to make a significant contribution to the provision of electricity independently in areas that have not been reached by the PLN network. In addition, active community involvement in the management and maintenance of PLTMH is a key factor in the success of this program. However, challenges such as limited funds, lack of technical support, and operational sustainability issues are still major obstacles. Therefore, synergy between the government, community, and private sector is needed to encourage the development of microhydro as a long-term solution to overcome the electricity supply crisis in remote areas.